Implementing Mindfulness-Based Mathematics Instruction to Reduce Mathematics Anxiety and Develop Problem-Solving Strategies among Fifth-Grade Students in Fraction Learning - Pratiwi, Nike; Atmoko, Adi; Taufiq, Ahmad; Alfaris, Renaldy; Faizah, Siti (Papanda Publisher, 2024)
Mathematics anxiety significantly impairs elementary students' problem-solving performance, yet instructional approaches that simultaneously address affective and cognitive dimensions remain underexplored. This qualitative single-case study examined the implementation of Mindfulness-Based Mathematics Instruction (MBMI) in one Grade V classroom in Malang, Indonesia, involving 28 students, of whom eight were selected as focal participants representing high, moderate, and low mathematics anxiety profiles. Data were collected across six 90-minute sessions through classroom observation, semi-structured interviews, think-aloud protocols, and document analysis, and were analyzed using thematic analysis supported by NVivo. Findings revealed three concurrent outcomes: consistent and progressively internalized MBMI implementation; a 58% reduction in observable anxiety-related behaviors across session phases, most markedly among high-anxiety students; and a qualitative shift in problem-solving strategies from impulsive computation toward structured, reflective engagement aligned with Polya's four-stage framework. An unanticipated finding identified language-processing demands in word problems as a distinct, non-computational source of situational anxiety. These results demonstrate that emotional regulation and metacognitive strategy development are dynamically interconnected within fraction instruction, positioning MBMI as a theoretically grounded and pedagogically feasible integrative approach for elementary mathematics classrooms.